2021
DOI: 10.1016/j.nedt.2021.105010
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing nursing students' intention to accept COVID-19 vaccination: A pooled analysis of seven European countries

Abstract: Background Experiencing the third wave of COVID-19 pandemic, high vaccination coverage by a safe and effective vaccine globally would be a great achievement. Acceptance of vaccination by nursing students is an important issue as they play a decisive role as future professionals in educating patients, counselling, and guiding them to the right clinical decision. Objectives To explore the intention of nursing students to get vaccinated for SARS-CoV-2 infection and the fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
74
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 46 publications
14
74
0
2
Order By: Relevance
“…Malik et al ( 2020 ) found that participants who had more trust in medicine got information from healthcare workers and health officials, whereas those who collected sources from social media had less trust in medical science. Similar results were found by Patelarou et al ( 2021 ), showing that those who got information from newspapers, television, radio, and government agencies had more trust in the COVID-19 vaccine than those who had self-perceived knowledge or collected information through social or online media. In fact, misinformation is more available on the internet where the information may be less accurate or verified (Liu and Yang, 2020 ; Obiała et al, 2020 ; Patelarou et al, 2021 ).…”
Section: Introductionsupporting
confidence: 85%
See 4 more Smart Citations
“…Malik et al ( 2020 ) found that participants who had more trust in medicine got information from healthcare workers and health officials, whereas those who collected sources from social media had less trust in medical science. Similar results were found by Patelarou et al ( 2021 ), showing that those who got information from newspapers, television, radio, and government agencies had more trust in the COVID-19 vaccine than those who had self-perceived knowledge or collected information through social or online media. In fact, misinformation is more available on the internet where the information may be less accurate or verified (Liu and Yang, 2020 ; Obiała et al, 2020 ; Patelarou et al, 2021 ).…”
Section: Introductionsupporting
confidence: 85%
“…Similar results were found by Patelarou et al ( 2021 ), showing that those who got information from newspapers, television, radio, and government agencies had more trust in the COVID-19 vaccine than those who had self-perceived knowledge or collected information through social or online media. In fact, misinformation is more available on the internet where the information may be less accurate or verified (Liu and Yang, 2020 ; Obiała et al, 2020 ; Patelarou et al, 2021 ). Skeptics also use online platforms to advocate vaccine refusal.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations